Diel dynamics and environmental influences on phytoplankton communities in an Andean lagoon: implications for management and conservation - Ivan Edward Biamont-Rojas; Herminio René Alfaro-Tapia (Acta Limnologica Brasiliensia)
Abstract: Aim Lacustrine environments are unique locations to study temporal fluctuations derived from natural and artificial sources within a hydrographic basin. The objective of this study was to analyze the diel cycle of physicochemical parameters and their influence on the phytoplankton community structure in open waters, as well as, to evaluate the total phosphorus and nitrogen contents in the vicinity of fish tanks in the lagoon, and to identify the phytoplankton assemblage in the water column in a diel cycle in an open water area during the rainy and dry seasons. Methods The epilimnion and hypolimnion zones of an open water area were assessed over 24 hours, starting at 10:00 on day one and finishing at 10:00 on day two, obtaining a total of 36 samples (9 samples at 3-hour intervals, in two lake zones, in two seasons). Sampling employed a Van Dorn sampling bottle, and the Morphologically Based Functional Groups (MBFG), Shannon-Weaver and Simpson Indices were employed to describe the identified genera. Results Six of the seven parameters monitored registered higher values during the rainy season; only transparency was higher during the dry season. Fifteen genera distributed in nine classes were identified, with richness and diversity being higher in the rainy season. Conclusions The MBFG and sinking properties of group and genera has influenced the vertical migration of phytoplankton. The daily cycle method effectively captured the fluctuations in physicochemical and phytoplankton parameters over a 24-hour period in both seasons in Chacas Lagoon.